Nutritional composition of six tropical grasses from the state of Jalisco, Mexico - Sosa-Montes, Eliseo; Mendoza-Pedroza, Sergio Iban; Huerta-Prado, Luis Angel; González-Cerón, Fernando; Silva-Luna, Manuel; Bárcena-Gama, José Ricardo (Ecosistemas y Recursos Agropecuarios, 2021)
The objective of this study was to evaluate the chemical composition of six forage grasses for the  Mexican wet and dry tropics: Andropogon gayanus, Andropogon gerardii, Cenchrus ciliaris, Chloris gayana, Megathyrsus maximus and Urochloa brizantha. Samples were collected on November 2019, in Tonaya, Jalisco, Mexico. Dry matter, ashes, crude protein (total and insoluble), ether extract, neutral detergent fiber, acid detergent fiber, hemicellulose, lignin and cellulose were determined. The evaluation was carried out at the Animal Nutrition Laboratory, Animal Science Department, Chapingo Autonomous University, Texcoco, State of Mexico. Each grass was evaluated, in triplicate, and each replicate was considered the experimental unit. Means of chemical composition were separated by the Tukey test (p < 0.05). The correlation between each pair of variables was estimated by the Pearson coefficient (p < 0.05). The higher the percentage of total protein (p < 0.05), the lower the percentage of ether extract and the higher the percentages of ashes and insoluble protein. Furthermore, the higher the percentage of insoluble protein, the lower the percentage of lignin (p < 0.05). Probably, protein concentrates in its insoluble fraction at the expense of ether extract and lignin. Consequently, great-blue-stem (Andropogon gerardii) showed high total protein (10.27%) and ashes (7.88%), and low percentages of lignin (5.23%) and ether extract (1.37%); but its insoluble protein was not as high (2.06%) as that of guinea grass (Megathyrsus maximus) (6.08%). Therefore, great-blue-stem had the best nutritional content at 35 días of regrowth.